2016
DOI: 10.1016/s2468-8967(16)30018-0
|View full text |Cite
|
Sign up to set email alerts
|

Developing Complete Ultrasonic Management of Kidney Stones for Spaceflight

Abstract: Bone demineralization, dehydration, and stasis put astronauts at an increased risk of forming kidney stones in space. The incidence of kidney stones and the potential for a mission-critical event are expected to rise as expeditions become longer and immediate transport to Earth becomes more problematic. At the University of Washington, we are developing an ultrasound-based stone management system to detect stones with S-mode™ ultrasound imaging, break stones with burst wave lithotripsy (BWL™), and reposition s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Future phantoms will continue to measure the effectiveness of additional features, refine the design, and form a basis for training. 18,19 We anticipate that the longer broader exposure of the SC-50 probe will make alignment and operation faster and easier, and its benefits even more dramatic in clinical use.…”
Section: Discussionmentioning
confidence: 99%
“…Future phantoms will continue to measure the effectiveness of additional features, refine the design, and form a basis for training. 18,19 We anticipate that the longer broader exposure of the SC-50 probe will make alignment and operation faster and easier, and its benefits even more dramatic in clinical use.…”
Section: Discussionmentioning
confidence: 99%
“…36 S-mode ultrasound was developed through the use of a standard flexible Verasonics® ultrasound system and the addition of a custom Density Ray Line Imaging algorithm, overlaid with targeted filtering and smoothing algorithmsa process known as spatial compounding). 35 Although S-mode ultrasound is still undergoing testing, early versions have demonstrated promising results: among renal stones <5mm and 5-10mm in diameter, sensitivity rates of 74% for stone detection and 70% for shadow detection have been observed; 74% of stone measurements and 88% of shadow measurements have fallen within 2mm of CT documented stone dimensions, suggesting good concordance by current terrestrial standards. 37 While the existing inflight management protocol for nephrolithiasis (pharmacologic intervention alone) may be effective for small stones, planning for upcoming long-duration interplanetary missions mandates the development of a treatment plan for larger stones, for which spontaneous passage is unlikely.…”
Section: Imaging In Spacementioning
confidence: 99%
“…In vivo studies in pigs have demonstrated the feasibility of real-time imaging feedback during BWL therapy, enabling the operator to monitor for injury while permitting visual confirmation of effective stone fragmentation. 35 By means of short, focused ultrasonic bursts, UP can be utilized to reposition stones within the collecting system. In an FDA feasibility study of 15 patients in the United States, stones were successfully moved (passed or repositioned to a target location) in 14 of 15 patients; no associated adverse events were reported.…”
Section: Imaging In Spacementioning
confidence: 99%
“…3 The technologies are being integrated into the NASA Flexible Ultrasound System to fly as medical and research equipment on future missions, and are being commercialized for patients on Earth. 4 With NSBRI funding, we performed a first-in-man study demonstrating that we can reposition stones of various sizes using transcutaneous ultrasound alone, without pain or adverse events. Clinical benefits included immediate natural expulsion of small stone fragments, diagnostic differentiation between a single large stone and a collection of fragments, and pain relief associated with moving a stone away from the ureteropelvic junction.…”
Section: To the Editormentioning
confidence: 99%